3 D Imaging and Structural Analysis of a Mesoporous‐Silica‐Body‐Supported Eggshell Cobalt Catalyst for Fischer–Tropsch Synthesis. Issue 18 (24th August 2016) - Han, Ting; Li, Xiaopeng; Lin, Chao; Zhang, Haojie; Gao, Peng; Zhao, Yonghui; Du, Fuping; Chen, Yuyun; Sun, Yuhan
Abstract: For understanding the relationship between the structure and catalytic property and further optimizing the synthetic steps, it is imperative to obtain basic information about the characteristics of heterogeneous catalysts, such as porosity, dispersion, and accessibility of the active metal phases. Herein, we reported a multiscale analysis of an eggshell‐Co‐based catalyst for the Fischer–Tropsch synthesis (FTS), which was prepared by wetness impregnation. Conventional characterization techniques, such as mercury porosimetry, nitrogen physisorption, and transmission electron microscopy (TEM), were employed for obtaining basic information about the porosity and dispersion of cobalt on the nanoscale; in addition, phase‐contrast X‐ray computed microtomography (X‐ray μCT) as a powerful method was employed for obtaining vitally complementary information regarding the 3 D structure of a millimeter‐sized mesoporous silica support and a full‐field view of the macroscopic distribution of cobalt. The Co reduction behavior and FTS performance was correlated with the structure analyses, highlighting the importance of simultaneously controlling the dispersion and spatial distribution of Co ranging from macro to nanoscale. Abstract : 3D mapping of eggshell catalysts : A comprehensive multiscale analysis of eggshell Fischer–Tropsch catalysts is presented. The spatial distribution of active Co species clearly exerts strong influence on the catalytic performance.